IDENTIFICATION OF DIGITAL DERMATOGLIPHY PROFILE IN THE 100M, 800M AND 3000M DASH RACE ATHLETS IN THE 17° JOGUINHOS ABERTOS DE SANTA CATARINA (Fiep Bulletin - online, 2014)
The sportive success depends mainly to the qualities prexistent in the athletes, the reserch of genetic indication become inevitable to the efficacy in the sportive activity. The Dermatogliphy studies the relief of the tip of the fingers of the hands and feet, being widely used for the detention of sportive talents and in the medicine to disclose anomalies, as hereditary shunting lines of behavior and problems. The purpose of the research was determine by a simple and reliable method, the athletes genetic aspect (Dermatoglyphic) of the 17th Mini Open Games of Santa Catarina at the competitions of 100m, 800m and 3000m dash. The protocol chosen for identification of the profile of Digital Dermatogliphy was the Protocol of Digital Dermatogliphy of CUMMINS & MIDLO (1942). The results of the research had shown the following profile of Digital Dermatogliphy. 100m dash: AL= 25%; ALW= 37,5%; 10L= 12,5%; LW= 12,5%; WL= 12,5%; A= 12,5%; L= 66,2%; W= 21,2% e D10= 10,8. In 800m dash: AL= 12,5%; ALW= 50%; 10L= 25%; LW= 12,5%; WL= 0%. A= 18,7%; P= 65%; W= 13,7% e D10= 9,5.To the 3000m dash: AL= 12,5%; ALW= 37,5%; 10L= 0%; LW= 25%;  WL= 25%; A= 10%; P= 55%; W= 35%; e D10= 12,5.
Keywords: Athletes; Profile; Digital Dermatogliphy